Production System Concept for Implementing Mass Customization Strategy in Furniture Industry - Dimkow, Svetoslav (International Journal of Industrial Engineering and Management, 2012)
This paper presents a production system concept for implementing mass customization strategy in furniture industry. The developed concept represents the characteristics of the European and Bulgarian furniture industries as well as the globalization’s impact on the furniture industry. The suggested production system concept is based on the development of organizations through partnership and the development and application of a strategy for mass customization in contract manufacture. The suggested conceptual solution for establishment of Suppliers Park would have a great importance for the Bulgarian furniture industry because each time more Bulgarian furniture enterprises turn to the idea of founding a contract manufacture. The suggested decision is a stage in a research project between Technical University Sofia and representatives of the Furniture Cluster in Bulgaria. Article history: Received (15 November 2012); Revised (02 December 2012); Accepted (07 December 2012)